Factorial design based preparation, optimization, characterization and in vitro drug release studies of olanzapine loaded PLGA nanoparticles. (12th December 2016) - Bohrey, Sarvesh; Chourasiya, Vibha; Pandey, Archna
Abstract: The objective of the present work was to develop and optimize olanzapine loaded polymeric nanoparticles using a factorial design. The presented work developed and optimized olanzapine loaded polymeric nanoparticles by using a 3 3 factorial design. The 3 3 factorial design was used for studying the effect of the main preparation variables on particle size and percent drug entrapment efficiency of the nanoparticles. A modified nanoprecipitation method was used to prepare nanoparticles successfully by using the biodegradable polymer poly(lactic- co -glycolic)acid (PLGA), and they were characterized for various parameters such as particle size, shape, zeta potential, percent drug entrapment efficiency, percent process yield and in vitro drug release behavior. Examination of the interaction between the excipients used as well as investigation of the nature of the drug, the formulation and the nature of the drug in the formulations was carried out by FTIR studies. Different kinetic models were used to analyze the in vitro drug release data. The preferred formulation showed a particle size of 127.6 ± 1.9 nm, PDI of 0.239 ± 0.013, zeta potential of −29.2 mV, entrapment efficiency of 72.46 ± 3.8% and process yield of 89.65 ± 1.3%. TEM results showed that these nanoparticles were spherical in shape and follow the Korsmeyer–Peppas model with different release exponent values.